Assessment of Digital Competencies in Initial Teacher Training in Chile: What Does the Research Say? - Silva-Quiroz, J (Springer Science and Business Media Deutschland GmbH, 2022)
The purpose of this study is to investigate research published on the evaluation of digital competence and digital teaching competence in teacher training in Chile. The objective is to reveal the types of studies, their theoretical conceptual references, what is assessed in them and the main contributions and findings for the strengthening of Initial Teacher Training. From a methodological point of view, a documentary meta-synthesis has been made of the content of research articles published in the last ten years in the WoS, Scopus, and SciELO databases. The search is organized into three categories: Digital Competence, Digital Teaching Competence, and Curriculum Frameworks. Articles are systematized considering the size and context of the participants in the study, purpose and instrument used, theoretical reference, evaluation areas, and results. The main findings of the study show a gap between high levels of Digital Competence and low levels of Digital Teaching Competence among Initial Teacher Training students, and an effort to incorporate these competencies into curricular frameworks. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.